Morphological and Cytological Characteristics of Tomato Plants (Solanum lycopersicum L.) Induced by Tapak Dara (Catharanthus roseus (L.) G. Don) Extract - Tri Wulandari; Ika Listiana; Ovi Prasetya Winandari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Polyploidy is commonly induced using antimitotic agents such as colchicine, which is imported and relatively expensive, therefore, alternative antimitotic agents derived from local resources are needed. There are three main classes of antimitotic agents: taxanes, vinca alkaloids, and colchicine. Taxanes are obtained only from the bark of the western yew plant, colchicine is derived from Colchicum autumnale L., and vinca alkaloids are obtained from the tapak dara plant (Catharanthus roseus). Therefore, the tapak dara plant has great potential as a source of antimitotic agents other than colchicine. This study aimed to determine the effect of tapak dara flower extract on the morphological and cytological characteristics of tomato plants (Solanum lycopersicum L.). The research used a completely randomized design with four treatment levels and five replications: P0 = control treatment, P1 = 0.05% concentration, P2 = 0.1% concentration, and P3 = 0.15% concentration, with a soaking duration of 10 hours. The observed parameters included germination percentage (%), plant height, number of leaves, number of flowers, and chromosome number. Data were analyzed using one-way ANOVA followed by Duncan’s multiple range test at the 5% significance level. The results showed significant effects on the number of leaves, number of flowers, and chromosome number. Treatment P1, with a concentration of 0.05%, was the best treatment.